Microbial population in the coelomic fluid of stichopus chloronotus and holothuria (mertensiothuria) leucospilota collected from Malaysian waters = Populasi Mikrob dalam Cecair Selom Stichopus chloronotus dan Holothuria (Mertensiothuria) leucospilota dari Perairan Malaysia - Lukman, Ahmad Lutfi; Nordin, Noor Faizul Hadry; Kamarudin, Kamarul Rahim (Penerbit UKM, 2014)
This preliminary study aimed to isolate and identify microbes that inhabit the coelomic fluid of two local species of sea cucumbers collected from Malaysian waters - a ‘gamat’ species i.e. Stichopus chloronotus Brandt, 1835 and the most abundant ‘timun laut’ species in Malaysia i.e. Holothuria (Mertensiothuria) leucospilota (Brandt 1835). Phylogenetic analyses of partial 16S rRNA mtDNA gene sequences suggested the presence of at least eight microbial genera i.e. five bacterial genera - Bacillus, Exiguobacterium, Pseudomonas, Stenotrophomonas and Vibrio - isolated from the coelomic fluid of H. leucospilota and three genera of gram-positive bacteria from the Micrococcaceae family - Kytococcus, Micrococcus and either Kocuria or Rothia - isolated from the coelomic fluid of S. chloronotus. We speculate that less diverse microbial population in S. chloronotus as compared to H. leucospilota could be due to a number of environmental factors e.g. penetration of light surrounding the habitats of both species, the feeding behaviour of H. leucospilota and the higher level of antimicrobial properties of coelomic fluid in S. chloronotus. In terms of antimicrobial-resistance capability test, an isolate from genus Pseudomonas that is suspected to be P. alcaligenes exhibited high resistance towards streptomycin. Another isolate from genus Stenotrophomonas that was suspected to be S. maltophilia showed moderate resistance towards streptomycin and lower resistance towards kanamycin. Both isolates were from the coelomic fluid of H. leucospilota. Tetracycline inhibited the growth of all bacterial isolates tested. Further studies with more specimens of S. choronotus and H. leucospilota from broader geographical locations and the use of complete mtDNA genes along with morphological approaches for species identification may facilitate to provide better insights into the microbial population in the coelomic fluid of both local sea cucumber species.